Pre Service Teachers’ Self-efficacy in Professional Competence Courses Offered at Faculty of Information Technology in a Private University in Salatiga - Krismiyati, Krismiyati; Tupessy, Pricilia Musesil; Yulia, Hanita (International Journal of Active Learning, 2020)
Having the belief of being competent in the subject area during the years of training are essential aspect for pre-service teachers. It will benefit them not only during their training or study but also when they are in their teaching duty. It tries to look at how the ICT pre-service teachers look at their own ability in relation to their professional competence which is Informatics Engineering and Computer subjects. This is a preliminary study in an effort to investigate pre-service teachers during their teacher education training. By looking at their self-efficacy in relation to their professional competence, recommendation could be made for future reference. This study employs quantitative method by using questionnaire for its data collection. It involves 130 pre-service teachers in their training. The result of the study shows that the dimensions of self-efficacy explored in this study show high interval for all three dimensions; its level, strength, and generality. This reflects that those pre-service teachers have high self-efficacy when they are attending the professional competence courses. This condition reflects that they will likely to be successful in carrying out their teaching duty provided they consistently have the high self-efficacy. Finally, some recommendations for further study are made so that this area could be more thoroughly explored.